Teoria konstytucji w świetle pozytywizmu instytucjonalnego - Weinberger, Ota (Wydział Prawa i Administracji UAM, 1993)
The author, founder (along with McCormick) of the conception of legal institutional positivism, considers the application of this approach to the explanation of some basic problems of t h e theory of constitution. In his considerations the author undertakes an "endurance test" of the application of institutional positivism to the analysis of selected problems of specialized legal disciplines.
The theory of constitution in light of institutional positivism